TINDAKAN-TINDAKAN HAMLET SEBAGAI REFLEKSI OEDIPUS COMPLEX DALAM DIRI HAMLET: SEBUAH PENDEKATAN PSIKOANALISIS - Destary Praptawati (Dinamika Bahasa dan Budaya, 2017)
Oedipus complex, a term in psychology, is known as a common topic in literature. This term named for Greek mythological character, King Oedipus who kills his father and marries his mother. Hamlet, a greatest work by William Shakespeare, is one of literary works which implicitly contains Oedipus complex issue. This issue is experienced by Hamlet as the tragic hero. To analyze his actions and prove that Hamlet suffers from Oedipus complex, this research used both psychoanalitic theory and Oedipus complex concept. As the result, it can be seen that Oedipus complex exists in Hamlet. This Oedipus complex is not explicitly revealed by Hamlet, but his thought and feeling lead his actions to reveal that he suffers from Oedipus complex. In this play, Oedipus complex is revealed through Hamlet’s actions toward people around him.Key: Oeipus complex, Hamlet, psychoanalitic theory